Interior Semantics Of The Lobby/Waiting Area In General Hospitals; A Preliminary Study - Ibrahim, Fuziah; Harun, Syarmila Hanim; Samad, Muna Hanim; Harun, Wan Mariah Wan (2008)

(untitled)
Semantics is the study of meaning in communication. The communication interprets in the study is between human and the artefacts in the immediate surrounding.